Issues of Media Trials in Iraqi after 2003 - مشكل الربيعي, بيداء سعدون; السراج, شكرية كوكز (ALBAHITH ALALAMI, 2017)
The Supreme Judicial Council decided on July 3, 2003, to set up a court to deal with the issues of publication and media. This court tries to solve the problems of media and publishing in both its civil and penal aspects. The decision of establishing the court represents a new and important step to be taken by the Iraqi Judicial Council for the tremendous development witnessed by media sector in general and press in particular especially after 2003. This study includes two main axes: the first one deals with the most important crimes of publication in the Iraqi legislations such as the crimes of defamation, libel, insult, indecency, and incitement; the second deals with an analytical survey of the completed cases i.e. the issues that obtain the decisive decision in the judgment. The discussed cases are about 150 cases. The study ends with a number of results which are as follows:1-The most important media cases considered by the court of media and publishing cases are civil cases and criminal cases, the first of which is field and gained the decisive decision in the ruling.2-The offenses of libel and slander are among the most common media offenses that are considered by the court of media publishing.3-The media personality is recorded in the forefront of the figures against which the charges are field in the court of media and publishing.4-The cases brought before the court of media and publishing are real and not malicious.